A new technique to enhance the position resolution of large area plastic scinitillators to reconstruct the cosmic muon tracks. (1st February 2022) - Sehgal, R.; Dey, R.; Behera, S.P.; Netrakanti, P.K.; Mishra, D.K.; Mulmule, D.; Jha, V.; Pant, L.M.
Abstract: In this paper, we present a study to use thick plastic scintillators to reconstruct the cosmic muon tracks, that can be used for the applications like Muon Tomography. At Bhabha Atomic Research Centre (BARC), India, a plastic scintillator array — `ISMRAN (Indian Scintillator Matrix for Reactor Anti-Neutrinos), ' with a total weight of 1.0 ton has been configured for neutrino physics study. Using the ISMRAN scintillators matrix, we present a technique of the position calibration of thick plastic scintillators using cosmic muons as a probe. The position resolution obtained from the cosmic muons based calibration method is compared with the one obtained from the traditional calibration method using the radioactive source. Finally, the accuracy of reconstructed cosmic muon tracks from the two position calibration techniques is compared using the χ 2 /ndf distribution of the fitted cosmic muon tracks.